2005
DOI: 10.1007/s10021-005-1221-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Boreal Lake Ecosystem during a Long-Term Manipulation of Top Predators

Abstract: We assessed the long-term (16 years) effects of introducing piscivores (northern pike) into a small, boreal lake (Lake 221, Experimental Lakes Area) containing abundant populations of two planktivorous fish species. After the introduction, pearl dace were extirpated and yellow perch abundance was greatly reduced. Daphnia species shifted from D. galeata mendota to larger bodied Daphnia catawba, but the total zooplankton biomass did not increase, nor did the biomass of large grazers such as Daphnia. Phytoplankto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…In the ElA lakes, the introduction of Northern Pike into naïve prey fish communities has consistently, in three independent experiments, resulted in a major initial restructuring of those communities (Elser et al 1998(Elser et al , 2000Findlay et al 2005) and, ultimately, as we have shown here, their apparent extirpation in these lakes. Although the extirpation of prey fish in lake 227 was known before this study, it was thought that lake 110 continued to support a remnant prey population and that lake 221 continued to support Yellow Perch based on surveys conducted during 1995-2000. our survey, more than a decade later, demonstrated otherwise.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In the ElA lakes, the introduction of Northern Pike into naïve prey fish communities has consistently, in three independent experiments, resulted in a major initial restructuring of those communities (Elser et al 1998(Elser et al , 2000Findlay et al 2005) and, ultimately, as we have shown here, their apparent extirpation in these lakes. Although the extirpation of prey fish in lake 227 was known before this study, it was thought that lake 110 continued to support a remnant prey population and that lake 221 continued to support Yellow Perch based on surveys conducted during 1995-2000. our survey, more than a decade later, demonstrated otherwise.…”
Section: Discussionsupporting
confidence: 57%
“…lake 222 has long-standing co-existing populations of Northern Pike, Yellow Perch, and minnows (Blacknose shiners, Notropis heterolepis) and was the source of many of the Northern Pike added to lakes 110, 221, and 227 (Elser et al 1998;Findlay et al 2005). Methods were identical to those described above, although we were unable to check the traps on the sixth day and assumed that the resultant catch on the seventh day was equally distributed over the twoday period.…”
Section: Survey Of Prey Fish Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulations of ELA lakes resulting in major changes in fish abundance and/or community composition have often not resulted in strong trophic cascades and responses of lower trophic levels were often delayed for several years (e.g. [33,57]). …”
Section: Discussionmentioning
confidence: 99%
“…Trophic cascades can cause large changes in fish-derived nutrient fluxes. For example, fish excretion in a planktivore-dominated lake supported 30% of primary production, but fish excretion in a piscivoredominated lake only supported 6-14% of primary production in a lake in Ontario, Canada (Findlay et al 2005). Similarly, Schindler et al (1993) calculated that fish excreted ;90% of P in a planktivore-dominated lake and ;20% of P in a piscivore-dominated lake in Michigan, USA (;80% by invertebrates).…”
Section: Invasive Lake Trout Disrupted Excretion Fluxes From Native Cmentioning
confidence: 99%